The region-of-origin effect in the purchase of wine: The moderating role of familiarity - García-Gallego, José Manuel; Chamorro-Mera, Antonio; García-Galán, María del Mar (Spanish Journal of Agricultural Research, 2015)
Research on the place-of-origin effect has proliferated in recent decades, although there are still gaps in this field, especially in relation to the region-of-origin (ROO) and to the influence of certain moderating variables on the effect. The purpose of this paper is to analyse the ROO effect in the purchase of wine, paying special attention to the moderating role played by familiarity. Via a survey of 427 consumers carried out in the region of Extremadura (Spain), the paper study how variables as the region's overall image, its image as a wine producer, the perceived quality of its products, and consumer ethnocentrism affect the intention to purchase regional wines. To reach that goal, a structural equation model was applied using the Partial Least Square technique to identify the variables that explain and moderate this intention. The results show the region's overall image (2.65% of contribution to the purchase intentions explained variance), its image as a wine producer (8.39%), the perceived quality of its products (22.42%), and consumer ethnocentrism (10.23%) to affect the purchase intentions directly and indirectly. The confirmation of a moderating effect of familiarity in one of the model relationships contributes to give answer to one of the most significant questions in marketing theory about the origin effect. These results have important managerial implications for policy decision-makers, confirming the value of implementing communication campaigns that pursue improvement of the region's image as a brand.